Avaliação da prevalência de doenças sistêmicas dos pacientes atendidos na Faculdade de Odontologia da Universidade Federal do Pará - BRITO, Hilda Fernandes (2019)
Introduction: Anamnesis and physical examination represent an great instrument of treatment, because diseases that were barely included in the dental clinic, today play an important role in diagnosis, prognosis and dental treatment. Many chronic and systemic diseases may compromise the success of treatment and should be discovered during the anamnesis.The objective of this study was to determine the prevalence of systemic diseases that most affect the patients attending UFPA's Dentistry Faculty. Methodology: The survey was carried out with 599 medical records by means of a questionnaire with questions history of diseases that the patient has had, genetics, if it makes use of some medication, if they are on medical treatment and if they are allergic to any substance.Results: it was observed that among 599 patient files analyzed, 380 (63.4%) were female and 219 (36.6%) were male. Among the systemic diseases contained in the form, allergy (13.4%), hypertension (7.7%) and joint problems (6.3%) were the most frequent pathologies. Discussion: Oral health is important as a component of the general individual's health. Because systemic diseases and medications are very common in dental clinics, the success of treatment is directly related to a good anamnesis, as well as the care and conduct therapy that can be adopted during dental treatment. Conclusion: Dental surgeons and students should be prepared to modify the planning and execution of dental treatment when faced with this type of situation, aiming at the well-being and health of the patient.